2020
DOI: 10.1002/mnfr.201901253
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Upregulates Hepatic Sex Hormone‐Binding Globulin Production by Increasing Adiponectin Through AKT/FOXO1 Pathway in White Adipose Tissue

Abstract: Scope Epidemiological studies have shown that caffeine increases serum sex hormone‐binding globulin (SHBG) levels. The relationship between caffeine and SHBG production has never been studied before at molecular level. The aim of this study is to examine whether caffeine regulates SHBG production and to determine the associated molecular mechanisms. Methods and results Two different studies are performed; in vitro studies using human HepG2 cells treated with caffeine (100 and 500 µm) and in vivo studies using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…47 Moreover, the results of in vitro assays showed that caffeine (100 and 500 µM) has no significant effect on the protein production of sex hormone-binding globulin (SHBG) in HepG2 cells, while in vivo experiments found that humanized SHBG transgenic mice administered oral caffeine (0.1 mg/mL) for 12 days clearly improved hepatic SHBG production, induced an increase in adiponectin, and upregulated the level of hepatocyte nuclear factor 4-alpha in human SHBG transgenic mice, suggesting that caffeine mediates the progression of different liver diseases through multiple pathways. 48 Caffeine is well known to have several mechanisms of action, the most prominent of which is to bind reversibly to ARs, blocking their action. However, it is currently reported that caffeine has antioxidant and pro-oxidation properties, so more in-depth research is needed.…”
Section: Cellular Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Moreover, the results of in vitro assays showed that caffeine (100 and 500 µM) has no significant effect on the protein production of sex hormone-binding globulin (SHBG) in HepG2 cells, while in vivo experiments found that humanized SHBG transgenic mice administered oral caffeine (0.1 mg/mL) for 12 days clearly improved hepatic SHBG production, induced an increase in adiponectin, and upregulated the level of hepatocyte nuclear factor 4-alpha in human SHBG transgenic mice, suggesting that caffeine mediates the progression of different liver diseases through multiple pathways. 48 Caffeine is well known to have several mechanisms of action, the most prominent of which is to bind reversibly to ARs, blocking their action. However, it is currently reported that caffeine has antioxidant and pro-oxidation properties, so more in-depth research is needed.…”
Section: Cellular Assaysmentioning
confidence: 99%
“…66 Moreover, caffeine solution (0.1 mg/mL) treatment for 12 days has been shown to significantly increase SHBG production in the liver and adiponectin levels in the epididymal adipose tissue of human SHBG transgenic mice. 48 Anti-fibrosis, anti-inflammatory, anti-infective, and anti-oxidant effects may explain the potential mechanism for the protective effect of caffeine on HCC induced by chemical poisons. Using macrophage-specific CD39 knockout mice, researchers found that cell-specific CD39 expression in macrophages and CD73 expression in HCC cells synergically activate the eATP-adenosine pathway, producing more adenosine, thereby impacting CD8 + T cell function and promoting anti-PD1 resistance, suggesting that targeted inhibition of adenosine alleviated HCC.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Coffee compounds can decrease chronic inflammation and, therefore, protect against DNA degradation, consequently decreasing the risk of disease [46]. The Wistar rats A medium roast of Coffea arabica (+) SOD, CAT, and GPx [36] Wistar rats Green Coffea arabica (-) Lipid peroxidation (+) GSH, SOD, CAT, and GR [35] Wistar rats Green Coffea canephora and caffeine (-) Carrageenan-induced paw oedema (Pergolizzi et al 2018) Wistar rats Green Coffea arabica (-) IL-1β, TNF-α, and Nos2 (-) Interstitial inflammation index [47] Humanized SHBG transgenic mice Caffeine (+) Hepatic SHBG production (-) Akt phosphorylation [77] Cross-sectional clinical trial Caffeinated beverages Coffee consumption positively associated with SHBG concentration [78] Prospective clinical trial Caffeinated and decaffeinated coffee (-) CRP, IL-6, and TNFR-2 (+) Adiponectin and SHBG (-) Estrone (+) Testosterone (-) C-peptide and IGFBP-3 [50] Prospective clinical trial Coffee intake (-) Urinary 8-OHdG (-) Ferritin [61] Prospective clinical trial Coffee intake (+) AhR (+) CYP1A1/A2 [65] Intervention clinical trial Green and roasted Coffea arabica blend (-) Spontaneous DNA strand breaks ( [57]; 2014; 2011)…”
Section: Anti-inflammation Effectsmentioning
confidence: 99%
“…Decreased SHBG may be linked to an elevated risk of PCa [50]. Coffee and caffeine are linked to greater SHBG concentration [50,77,78]. Caffeine and SHBG are primarily metabolized by the liver, so one possible explanation is that caffeine intake might cause SHBG rise by impacting its catabolism [50].…”
Section: Controlling Steroid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation